(untitled) (Research, Society and Development, 2022)
The study addresses the issue of students with Attention Deficit Hyperactivity Disorder (ADHD). This is a topic that has drawn the attention of researchers and educators in the context of inclusive education. It is understood that in Brazil there is a paradox between what the laws proclaim and what is actually carried out in practice. Unprepared schools, teachers with deficient training and cultural barriers appear as obstacles to be overcome in an inclusive perspective of education. The study aimed to address the challenges of school inclusion of students with ADHD. This is a bibliographic, qualitative, exploratory and explanatory study. A multi-case study is also part of the methodological framework of the study, which were selected from the Digital Library of Theses and Dissertations database. The study showed the following results: a) the existence of an application to help young people and adults with ADHD in carrying out their daily tasks; b) a study that showed that the use of methylphenidate is related to the performance of students who use this drug, and; c) the use of the decision tree for complaints of lack of attention and hyperactivity in early childhood education. The study concludes that the theme of ADHD in education needs to be further discussed in terms of its debate and suggests family participation as a way to make the school inclusion of students who are in this condition more fruitful and who, like non-specialty students need to progress in their studies. The challenge of an education with an inclusive approach is to guarantee access and permanence of special students in the educational system with a view to achieving their training for life and for the exercise of citizenship.